2019
DOI: 10.1155/2019/3954890
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk between Fat Homeostasis and Liver Regional Immunity in NAFLD

Abstract: The liver is well known as the center of glucose and lipid metabolism in the human body. It also functions as an immune organ. Previous studies have suggested that liver nonparenchymal cells are crucial in the progression of NAFLD. In recent years, NAFLD's threat to human health has been becoming a global issue. And by far, there is no effective treatment for NAFLD. Liver nonparenchymal cells are stimulated by lipid antigens, adipokines, or other factors, and secreted immune factors can alter the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 119 publications
2
15
0
1
Order By: Relevance
“…A vicious cycle is formed due to excessive production of FFA in body and leads to the increase of liver TG. 23 The accumulation of FFA in muscle and liver induced by increased lipolysis in turn interferes insulin's utilization, glucose metabolism and causing IR. 24 The peripheral tissue glucose uptake and utilization capacity are decreased by IR, 25 and excess glucose reaches the liver through blood circulation and deposits in the form of TG.…”
Section: Discussionmentioning
confidence: 99%
“…A vicious cycle is formed due to excessive production of FFA in body and leads to the increase of liver TG. 23 The accumulation of FFA in muscle and liver induced by increased lipolysis in turn interferes insulin's utilization, glucose metabolism and causing IR. 24 The peripheral tissue glucose uptake and utilization capacity are decreased by IR, 25 and excess glucose reaches the liver through blood circulation and deposits in the form of TG.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, upper body fat accumulation resulted in increased free fatty acid release [22,23] and increased cytokines and adipocytokines production [24], which played an important role in the pathogenesis of NAFLD, namely, the "two hits" theory. Furthermore, the activation of carbohydrate response element binding protein and sterol regulatory element binding protein-1c upregulated glycolytic enzymes and fatty acid synthase to promote hepatic lipogenesis in obesity [25]. In addition, there was complex crosstalk between fat homeostasis and the liver regional immune system.…”
Section: Men Womenmentioning
confidence: 99%
“…Thus, it becomes imperative to study the initiation and the progression of NAFLD through its various phenotypic stages to devise efficient and robust intervention measures to control the spread of this epidemic. Multiple studies have shown the importance of various key regulators and genetic alterations for the development and the progression of NAFLD [67,68]. However, there are only a few attempts to analyze NAFLD from a systems biology perspective, i.e., decoding how these different regulators interact in the context of NAFLD [17,[69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%